Modelo estendido de adoção da tecnologia de comunicação pessoal de voz pela internet - Cappellozza, Alexandre (2013)
Scientific studies have shown the existence of several factors that influence the adoption process of Information Technology. Different aspects related to the intended use technologies seem to be present in decisions about technology adoption, for example, relative advantages obtained by the use of technology, knowledge required for the operation of systems, ease of use and usefulness of technology, among others. Consequently, technology suppliers can also pursue business strategies that attract users through offers that include subsidies, discounts, such as phone carriers. However, there are scientific studies showing that the process of technology adoption may not be explained only by economics aspects but, also, include behavioral ones. Theories focused on adoption technology models can explain a portion of the reasons that lead individuals to behave in accordance with the use of a particular technology. For example, individual habit, accessibility and convenience may influence the preferences of a particular use of information technology. In this sense, users may manifest resistance on the use of available technologies, where this resistance can be justified from negative perceptions that would form a barrier to adoption of information systems. Therefore, one of the technology segments that present conditions with multiple features is the technology of voice communication, where the user can communicate via wired lines, mobile phones, Internet, among other ways. Thus, it is possible to analyze influences, including behavioral ones, where individuals can express decisions which show others reasons, besides the exclusive pursuit of economic results, on the use of personal communication technologies. In order to implement those analysis, we chose to contextualize the study focused on the technology of Voice over IP - VOIP as compared to other communication technologies, can be presented as one of the benefits major economic: free-calls between users of a system, coupled with other benefits emanating from the telephony technology itself. The results from this study have demonstrated VOIP individual adoption receives influences from several factors, positioned in different dimensions. For instance, individual perceptions about the characteristics of technology, user network and habits, besides commercial incentives toward concurrent communication technologies usage may create an individual subjective network of perceptions to the VOIP telephony adoption over the benefits that may be gathered from this application.